Functional and structural kidney alterations associated with fertility drug administration in rats - Ibtihal Kadhim Mazyed; Fatima Aziz Mahdi Al-badry (Український Журнал Нефрології та Діалізу)
Fertility stimulants are medications used to enhance reproductive fertility in both men and women. Clomiphene citrate (Clomid), Duphaston, and Procreation V are commonly used fertility drugs. However, their prolonged use has been associatd with adverse effects, including histological and biochemical changes in the liver and kidney. This study aimed to evaluate renal changes in structure and function following infertility drug administration.